Eficiência do peróxido de hidrogênio no pré-tratamento do resíduo industrial da macaúba (Acrocomia aculeata) para produção de etanol 2G - Wanderley, Romualdo Julio Cavalcante (Universidade Federal do Tocantins, 2022)
The objective of this work was to evaluate the efficiency of hydrogen peroxide in the pre-treatment of industrial residues Mesocarp + Extruded Peel (Meso + Ext Peel) and extruded Almond (Ext Almond) from macaúba (Acrocomia aculeata) for the production of 2g ethanol. The concentrations of neutral detergent fiber, acid detergent fiber, lignin, hemicellulose and cellulose in the biomass before pretreatments were quantified. The treatments evaluated were the effects of pre-treatments with alkaline hydrogen peroxide (H2O2, 5% v/v) and with distilled water (H2O2), on the fibrolytic and amylolytic enzymatic hydrolysis coefficients of the biomasses (Meso + Ext Peel and Almond Ext) from Macaúba. The pre-treatment residue underwent enzymatic hydrolysis and later the estimation of the potential for ethanol production was performed by the glucose concentration obtained after hydrolysis, using the Gay-Lussac equation. The effects of pre-treatment with H2O2 on Meso + Peel Ext and Almond Ext biomass influenced the increase in the fiber enzymatic hydrolysis coefficient. In the starch hydrolysis, there was no significant difference between the pre- treatments. In this hydrolysis, precipitation of material occurred, thus verifying a negative effect on its coefficient. The increase in the fiber hydrolysis coefficient did not result in significant availability of free glucose in the wort, given the reduced levels of hydrolysable cellulose found in both biomasses. Therefore, submitting them to the process of obtaining ethanol may not be the best way.